Phantom tumor of the lung - Dávila-Hernández, Dávila-Hernández (2020)
A 95-year-old female patient with nocturnal dyspnea, dry cough and 39.2 °C fever for six days and a history of adverse reaction to acetaminophen and clarithromycin; hypertensive and controlled with losartan. On examination: PA 100/60 mm Hg, heart rate 90 beats/min, breathing rate 22 excursions/ min. Lower limbs oedema. Lungs: vesicular murmur decreased at both bases. Cardiovascular: rhythmic, low-intensity heart sounds. Rest of the exam was normal. Chest x-ray revealed a dense, homogeneous, oval nodular image in the left lung. The CT scan showed a pleural effusion in the left oblique fissure. It was treated as decompensated heart failure. Five days, the chest x-ray showed no nodular image described so the diagnosis of phantom tumor of the lung was confirmed.